An improved thermo-mechanical model for spindle transient preload analysis. (November 2019) - Li, Jiandong; Zhu, Yongsheng; Yan, Ke; Hong, Jun; Yan, Xiaoyun
Preload has a significant effect on the precision of machine tool spindle, and it changes transiently in different operating conditions. In this paper, the transient feature of spindle preload under multi-factor coupled effect was discussed theoretically and experimentally. By adopting the transient network method and the time-discrete approach, the integrated thermo-mechanical model of a spindle was established. The axial and radial deformations of spindle system, induced by centrifugal force, thermal, and assembly stresses, were all discussed. The effects of the various factors on the transient preload were analyzed, and results show that speed and temperature contribute the most to the transient preload, followed by the bearing deflection. Finally, experimental results indicate the correctness of the improved model.